1994
DOI: 10.1530/jrf.0.1010327
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and culture of human endometrial cells in a three-dimensional culture system

Abstract: A cell culture system was established in which endometrial stromal cells were embedded in a collagen matrix and separated from the endometrial epithelium by basement membrane material (Matrigel). The epithelium, seeded on top of the collagen matrix, grew in a monolayer. The cultures were evaluated by light microscopy and transmission and scanning electron microscopy. Light and transmission electron microscopy indicated a polarized columnar epithelium in monolayer with basally positioned nuclei. Scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 7 publications
1
57
0
Order By: Relevance
“…A few studies have used in vitro models of human implantation that focused mainly on ultrastructural relationships between the attached blastocyst and the endometrial epithelium, e.g. in a three dimensional cell culture system [81][82][83][84]. Carver et al [85] demonstrated hCG-secreting activity of a blastocyst implanted into endometrial stromal cells monolayer.…”
Section: Model Of Early Embryonic Implantationmentioning
confidence: 99%
“…A few studies have used in vitro models of human implantation that focused mainly on ultrastructural relationships between the attached blastocyst and the endometrial epithelium, e.g. in a three dimensional cell culture system [81][82][83][84]. Carver et al [85] demonstrated hCG-secreting activity of a blastocyst implanted into endometrial stromal cells monolayer.…”
Section: Model Of Early Embryonic Implantationmentioning
confidence: 99%
“…Present knowledge relies partly on in vitro models in which embryos, or trophoblastic spheroids derived from cell lines, primary tissue or embryonic stem cells, attach to 2D or 3D cultures of endometrial epithelium from either primary tissue or cell lines (Bentin-Ley et al, 1994;Boggavarapu et al, 2016;Hannan et al, 2009;Kang et al, 2015Kang et al, , 2014Lalitkumar et al, 2013;Lee et al, 2015;Singh and Aplin, 2015;Singh et al, 2010;Weimar et al, 2013). Recent observations of embryos attaching directly to cell-free surfaces demonstrate their self-organising potential (Deglincerti et al, 2016;Shahbazi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in vitro three-dimensional culture systems have been established in which epithelial and stromal cells are co-cultured. The epithelial cells exhibit polarity, with microvilli and pinopodes, and closely resemble endometrium in vivo (Bentin-Ley et al, 1994). These systems offer the potential for studying the local molecular events involved in blastocyst adhesion in vitro, and for elucidating the role played by cytokines in producing an attachment competent luminal epithelium.…”
Section: Summary and Future Prospectsmentioning
confidence: 99%